Psychopathology in patients with psoriasis: a cross-sectional clinical study - Padma, Kumari; Nanaware, Sagar Subhash; Yadihal, Aruna; Mathai, P. John (International Journal of Research in Medical Sciences, 2019)
Background: Psoriasis is associated with a variety of psychological problems including poor self-esteem, sexual dysfunction, anxiety and depressive disorder and suicidal ideation. There are reports that patients with psoriasis may have significant psychiatric morbidity. The objective of the study is to evaluate the frequency of psychiatric disorders, frequency and nature of psychiatric symptoms in patients with psoriasis. Methods: 100 patients with psoriasis were evaluated and included for the study. Comprehensive Psychopathological Rating Scale (CPRS) is used for assessment of psychiatric symptoms and MINI Plus for assessing psychiatric disorders. Chi-square test was used to compare the proportions. Results: Patients with psoriasis had high frequency of psychiatric morbidity and was found to be 42%. Conclusions: Patients with psoriasis have more psychopathology and higher psychiatric morbidity which may further imply justifiable consultation liaison psychiatry in other speciality fields like Dermatology.